(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the importance of the practical use of the educational process together with modern educational technologies, modern information technologies entering the education sector of our country, achievements and their results.